Farming First at CSD-17—Dr. James Hansen, Columbia University - Hansen, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2009)
Dr. James Hansen discusses how agriculture is being rediscovered by the global policy community as a key driver for more sustainable economic development. To escape this persistent poverty trap, Hansen argues that farmers have only their labour, their intelligence and their land at their disposal. Meanwhile, climate change is changing the external conditions which influence farmers' decision-making. As a result, he argues that global policy needs to reflect these realities and empower farmers to improve their livelihoods through an enabling policy environment.